A novel negative thermal expansion material of Zr0.70V1.33Mo0.67O6.73. Issue 7 (16th January 2017) - Zhang, Mengdi; Mao, Yanchao; Guo, Juan; Zhou, Wenjin; Chao, Mingju; Zhang, Niu; Yang, Mengjie; Kong, Xuhui; Kong, Xiaoshuai; Liang, Erjun
Abstract : A novel negative thermal expansion (NTE) material of Zr0.70 V1.33 Mo0.67 O6.73 was synthesized. Abstract : A novel negative thermal expansion (NTE) material of Zr0.70 V1.33 Mo0.67 O6.73 was synthesized. Its microstructure, crystal structure and thermal expansion properties were studied in detail. Structure analysis shows that Zr0.70 V1.33 Mo0.67 O6.73 possesses a cubic crystal structure with the space group Pa 3̄ (no. 205) at room temperature (RT). The experimental results show that Zr0.70 V1.33 Mo0.67 O6.73 exhibits a stable isotropic negative thermal expansion property and maintains a cubic structure from 103 to 773 K without any phase transition. The average linear coefficients of thermal expansion (CTEs) are calculated to be −3.75 × 10 −6 K −1 (163–673 K) and −4.50 × 10 −6 K −1 (RT–773 K). The intrinsic linear CTEs are calculated to be −3.84 × 10 −6 K −1 (103–473 K) and −4.22 × 10 −6 K −1 (RT–673 K). And the phase transition temperature of ZrV2 O7 has been reduced below RT, this may be attributed to the incorporation of the cubic ZrMo2 O8 structure and partially occupied Zr atoms (4a). The NTE property of Zr0.70 V1.33 Mo0.67 O6.73 can be attributed to the quasi-rigid unit modes (QRUMs).